Prenatal ultrasound scoring in diagnosis and postpartum outcomes prediction for Placenta Accreta Spectrum (PAS): a systematic review - Xue Peng; Xi Tan; Zhao Wu (BMC Pregnancy and Childbirth)
Abstract Background Placenta accreta spectrum (PAS) is one of the most dangerous pregnancy-related conditions. This study aims to conduct a systematic review of current research on the ultrasound scoring systems used in PAS patients with a comprehensive summarization of researches and comparison of prenatal ultrasound scoring in evaluating postpartum outcomes. Methods This systematic review was conducted and reported following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Studies were retrieved from four databases (PubMed, Cochrane Library, Embase and Web of Science) up to December 2023. Original studies involving women diagnosed with PAS using ultrasound scoring for diagnosis or outcome evaluation were screened based on predefined inclusion and exclusion criteria. The primary outcome was the diagnostic performance of ultrasound scoring systems and their effectiveness in predicting labor outcomes. The Quality Assessment of Diagnostic Accuracy Studies-2 (QUADAS-2) tool was utilized to assess the study quality. The study has been registered on the PROSPERO website with the registration number CRD42024507311. Results Sixteen studies met the inclusion criteria. 3930 patients were included in the review, with 1693 participants in the control group. Included studies had a high risk of bias in patient selection, with a low risk in flow and timing and reference standards. Existing studies have reported several indicators that can be included in ultrasound scoring systems and tested their effectiveness in diagnosis and severity evaluation. The pool sensitivity, specificity, and area under the curve (AUC) of ultrasound scoring system in diagnosing PAS were 0.89 (95% confidence interval [CI]: 0.82–0.94), 0.85(95%CI: 0.80–0.90) and 0.93 (95%CI:0.91–0.95). Ultrasound scores are associated with PAS outcomes including intraoperative haemorrhage, postpartum haemorrhage, hysterectomy, length of hospital stay, and neonatal prognosis. Limitation is that the existing studies are wide-ranging but have low replication and association. Conclusion Ultrasound scoring systems play a role in the prenatal diagnosis, management, and prediction of postnatal complications in PAS. Nevertheless, additional research is required to further evaluate the performance between different scoring systems to develop a unified consensus.